Elaboracion de un plan de reforestación de las cuencas hídricas del Páramo Capulis paso para mantener la captación de agua de consumo humano en la parroquia Belisario Quevedo cantón Latacunga provincia de Cotopaxi - Yanchatipán De la Cruz, María Belén (2012)
The moorland of Ecuador are large tracts of land they occupy approximately 5% of the national territory, are ecosystems that are very rich in its biodiversity, a flora and fauna that is eachdiagnosis of, also have natural attractions which are appreciated by insiders and outsiders. Capulis Paso moorland, which is placed in Juan Montalvo parish, Latacunga city, is a strategic place for water production because it has a high potential to offer the country in providing environmental services. The proposed objectives and activities designed in the project, involve the participation of public, private institutions and civil society (“Parroquia Belisario Quevedo” Water Committee) committed to the conservation of the moors, for the creation of alternative sustainable management of natural resources....